WhatsApp and Google Drive Influence on Pre-service Students’ Learning - Moreno-Guerrero, Antonio-José; Rodríguez-Jiménez, Carmen; Ramos-Navas-Parejo, Magdalena; Soler-Costa, Rebeca; López-Belmonte, Jesús (Frontiers in Education, 2020)
The use of technology and all that it entails, such as applications and social networks, has led to a transformation of education in all aspects. Communication and the monitoring of training processes are being transformed through these new elements gradually incorporated into the classrooms. The aim of the study is to analyse the impact of WhatsApp and Google Drive on the monitoring of training practices among pre-service students using a traditional, face-to-face methodology. A quasi-experimental design was carried out on a sample of 123 Spanish pre-service students. The data were collected by means of a questionnaire. The results show that the follow-up of external practices of future teachers using WhatsApp and Google Drive is effective in comparison with the face-to-face follow-up, although no significant differences are shown in the students' grades. Conclusions show that applying a monitoring method with these technological tools leads to an increase in students’ motivation mainly as it allows a more direct interaction between the teacher and the student. It is important to select the monitoring method and the target student in the didactic development. Hence, these educational applications enable active learning where the learner is the main protagonist and can be supported and monitored.